Parámetros de procesos en la obtención de mermelada mixta de piña (Ananas comosus) y carambola (Averrhoa carambola) - Tejada Arbildo, Daniel Agustin (2025)
The thesis aimed to the preparation and characterization of a mixed jam based on pineapple (Ananas comosus) and star fruit (Averrhoa carambola), fruits naive to the Peruvian Amazon rich in their high content of bioactive compounds. It was developed in the laboratories of CIRNA and FIA-UNAP. Physicochemical analyses of the raw materials were carried out, evaluating parameters such as moisture content up to vitamin C. The results obtained showed a standard deviation of less than 1.0, which guarantees high reliability in the data. Subsequently, a standardized flow chart was developed for the production of the mixed jam, after which the physicochemical analyses of the final product were carried out following the methods established by the AOAC (2018). The values obtained were: water: 8.65%, titratable acidity 0.32%, pH 3.55, Brix degrees 65.00%, and vitamin C 117.00 mg/100 g. Likewise, microbiological analyses were carried out according to the ICMSF methodology (2012), detecting fungal and yeast counts below < 10 CFU/g, indicating an adequate safety of the product 203.047-1991 (Rev. 2017). Regarding the sensory assessment, it was carried out using the scoring methodology proposed by Hernández (2005), determining that the T3 treatment obtained the greatest acceptance by the evaluators. Finally, the statistical data showed that there was no significance in the treatments, suggesting a homogeneity in the treatments evaluated.